The animation studies reader - Dobson, Nichola 1976-; Honess Roe, Annabelle; Ratelle, Amy 1976-; Ruddell, Caroline (Bloomsbury Academic, 2019)
"The first collection of definitive texts that explores and examines key areas of animation studies through three points of focus: theoretical approaches; form and genre; issues of representation"...
Includes bibliographical references and index
Keywords: Animated films -- History and criticism; Animated television programs -- History and criticism; Computerfilm; Zeichentrickfilm; Computeranimation; Animationsfilm; Aufsatzsammlung